2019
DOI: 10.1021/acs.molpharmaceut.9b00396
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Delivery and Biodistribution Analysis of an Antibody–Enzyme Fusion for the Treatment of Lafora Disease

Abstract: Lafora disease (LD) is a fatal juvenile epilepsy, characterized by the accumulation of aberrant glucan aggregates called Lafora Bodies (LBs). Delivery of protein-based therapeutics to the central nervous system (CNS) for the clearance of LBs remains a unique challenge in the field. Recently, a humanized antigen-binding fragment (hFab) derived from a murine systemic lupus erythematosus DNA autoantibody (3E10) has been shown to mediate cell penetration and has been proposed as a broadly applicable carrier to med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Preclinical studies of LD therapeutics are currently underway with multiple lines of treatment in development ( Brewer and Gentry, 2018 ; Brewer et al., 2019a ; Gentry et al., 2020 ). The first published therapeutic strategy uses an antibody-enzyme fusion that degrades LBs, the toxic carbohydrate aggregates that cause LD ( Austin et al., 2019 ; Brewer et al., 2019b ; Zhou et al., 2019 ). This drug is administered directly into the central nervous system, eliminating brain LBs and correcting the cerebral metabolic phenotype in LD mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies of LD therapeutics are currently underway with multiple lines of treatment in development ( Brewer and Gentry, 2018 ; Brewer et al., 2019a ; Gentry et al., 2020 ). The first published therapeutic strategy uses an antibody-enzyme fusion that degrades LBs, the toxic carbohydrate aggregates that cause LD ( Austin et al., 2019 ; Brewer et al., 2019b ; Zhou et al., 2019 ). This drug is administered directly into the central nervous system, eliminating brain LBs and correcting the cerebral metabolic phenotype in LD mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward, new mutations can be quickly classified using our empirical pipeline and distinguished from benign polymorphisms. Our results showed that this system can be used to guide patient-specific clinical care and the deployment of therapeutics, which is needed to maximize the benefit from emerging LD therapeutics (Austin et al, 2019;Brewer and Gentry, 2018;Brewer et al, 2019aBrewer et al, , 2019bGentry et al, 2020;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…Excitingly, preclinical studies of LD therapeutics are currently underway with multiple lines of treatment in development [34][35][36] . The first published therapeutic strategy utilizes an antibodyenzyme fusion that degrades LBs, the toxic carbohydrate aggregates that cause LD [37][38][39] . This drug is administered directly into the CNS, eliminating brain LBs and correcting the cerebral metabolic phenotype in LD mouse models.…”
Section: An Empirical Pipeline For Personalized Medicinementioning
confidence: 99%
“…Moving forward, novel mutations can be quickly classified using our empirical pipeline and distinguished from benign polymorphisms. This system can be used to guide patient-specific clinical care and the deployment of therapeutics, which is needed to maximize the benefit from emerging novel LD therapeutics that are being developed [34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…He then focused on recent work from his laboratory performed in collaboration with Valerion Therapeutics. They developed a novel antibody-enzyme fusion (AEF) that employs an antibody fragment with cell penetrating properties fused to an amylase that can degrade LBs [21][22][23]. Gentry showed that the AEF, termed VAL-0417, robustly degrades LBs in vitro releasing glucose and maltose.…”
mentioning
confidence: 99%